Hybrid NRZ/RZ line coding scheme based hybrid FSO/FO dual channel communication systems - Mahmoud M. A. Eid; Ahmed Nabih zaki Rashed (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This study simulates the hybrid non return to zero (NRZ)/return to zero (RZ) line coding scheme based hybrid free space optics (FSO)/fiber optics (FO) dual channel communication systems. The max Q factor/Min BER are simulated after APD receiver based both erbium doped fiber amplifiers (EDFAs) and wide band traveling wave semiconductor optical amplifiers (WBTWSOAs) with 50 km fiber channel and 4 km FSO channel. Max SPAL/min noise SPAL, max signal power amplitude/min noise signal power variations with spectral frequency, and the total electrical power are demonstrated and clarified in this proposed study. This work emphasized that the fiber channel is reached up to 100 km reach and FSO channel can be also extended to 4 km reach with 40 Gbps.